A Study on Communication Practices in Reducing Non-Communicable Diseases in Bahir Dar City, Ethiopia - Tefera YD; Ali AC; Woldearegay AG (Dove Medical Press, 2024)
Yekitie Dagne Tefera,1 Adem Chanie Ali,1 Amanuel Gebru Woldearegay2 1Department of Journalism and Communication, Bahir Dar University, Bahir Dar, Ethiopia; 2School of Journalism and Communication, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Yekitie Dagne Tefera, Tel +251-910152077, Email yekitieaynalem@yahoo.comBackground: Non-communicable diseases (NCDs) pose special challenges in developing countries In Ethiopia, the growing NCD burden has raised a public health concern with significant social, economic, and developmental effects. Thus, the study sought to examine health communication practices in addressing the NCDs in Bahir Dar City of the Amhara Region of Ethiopia.Methods: A qualitative case study was conducted from January to April 2023. The study employed in-depth interviews, focus group discussions, and observations to gather data from health extension workers, NCD experts, and NCD focal persons about their experiences and perspectives regarding NCD prevention and control. The participants were purposively selected, and a thematic analysis technique was employed to analyze the data.Results: The study found that several health communication strategies, such as health promotion, training and creating model households, screening, referrals, follow-ups, rehabilitation services, and activities reporting were employed. Nevertheless, there was a lack of consistent, reliable, and long-lasting and professional health communication regarding NCD prevention and management. Some of the challenges contributing to such deficient practices were overloading HEWs with various tasks, allocating many households to a single HEW, shortage of screening tools, shortage of financial and human resources, weak interdisciplinary collaboration, COVID-19, and recurrent conflicts in the city and the region. Above all, lack of health communication skills affected the health interventions. Concerning communication methods, one-to-one communication was frequently employed, while mass media and social media were rare. Generally, NCD communication, in particular, and health communication, in general, did not receive priority as other health-related activities in the city.Conclusion: The study found that there were poor health communication practices in preventing and controlling NCDs. Thus, professional practice of health communication about NCDs must be prioritized, and emphasis should be given to inter-sectoral collaborations. Prioritizing financial and human resources is also essential for effective NCD communication.Keywords: health communication, health extension workers, communication strategies, communication methods, non-communicable diseases, risk factors